2022
DOI: 10.3389/fmars.2022.823006
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Variability of the Feeding Conditions for the Norwegian Spring Spawning Herring in May

Abstract: The abundant and ecologically important copepods Calanus finmarchicus and Calanus hyperboreus within the Norwegian and Iceland Seas are key prey species of Norwegian spring spawning herring. The volume flux of East Icelandic Water, which carries the mentioned zooplankton species into the southern Norwegian Sea, is highly variable. The years 1996–2002 have previously been characterized as high influx years, 2003–2016 as low influx years and since 2017 a reversal to higher influx has been apparent. Hydrographic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…First, the fueling of zooplankton via the EIC (Wiborg, 1954;Kristiansen et al, 2022). Kristiansen et al (2019) found a coinciding decrease of MEIW and C. hyperboreus abundance at Section N in the early 2000s but an increase of C. hyperboreus since 2017 within the southwestern Norwegian Sea (Kristiansen et al, 2022). This paper shows that the increase in C. hyperboreus abundance with increasing Arctic Waters can also be traced to the eastern part of the Norwegian Basin (Figure 9).…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…First, the fueling of zooplankton via the EIC (Wiborg, 1954;Kristiansen et al, 2022). Kristiansen et al (2019) found a coinciding decrease of MEIW and C. hyperboreus abundance at Section N in the early 2000s but an increase of C. hyperboreus since 2017 within the southwestern Norwegian Sea (Kristiansen et al, 2022). This paper shows that the increase in C. hyperboreus abundance with increasing Arctic Waters can also be traced to the eastern part of the Norwegian Basin (Figure 9).…”
Section: Discussionmentioning
confidence: 72%
“…Related to the changes in the Arctic Water two partially related mechanisms are at play. First, the fueling of zooplankton via the EIC (Wiborg, 1954;Kristiansen et al, 2022). Kristiansen et al (2019) found a coinciding decrease of MEIW and C. hyperboreus abundance at Section N in the early 2000s but an increase of C. hyperboreus since 2017 within the southwestern Norwegian Sea (Kristiansen et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…We only used data from the North Sea (51.5°N -62.0°N and 4.0°W -8.0°E) and Skagerrak-Kattegat (east of 8.0°E). Further, we only included abundance data of Calanus finmarchicus, C. helgolandicus, and large and small copepods which are important prey items for herring and sprat (Falkenhaug and Dalpadado, 2014;Kristiansen et al, 2022). Small copepods (<2 mm) were identified based on the "traverse" counting method, i.e.…”
Section: Zooplanktonmentioning
confidence: 99%
“…The variability in the Norwegian Sea Gyre is linked to the input of colder East Icelandic water into the Norwegian Sea. This, in turn, governs the relative contribution of both C. hyperboreus and large overwingering stages of C. finmarchicus, which are both important as prey to herring early in the feeding season (Kristiansen et al, 2019;Kristiansen et al, 2022). The influx of subarctic waters from the Iceland Sea is also a key nutrient source for the Norwegian Sea (Skagseth et al, 2022).…”
Section: Possible Links To Oceanography and Lower Trophic Levelsmentioning
confidence: 99%
“…The Jan Mayen front has been identified as an important transitional zone in both zooplankton biomass, abundance and diversity, changing significantly across the front (Melle et al, 2020). Both prey abundance and stomach content of herring was higher on the western, colder side of the front (Melle et al, 2020;Kristiansen et al, 2022), where Calanus hyperboreus was important part of the diet. On the Atlantic side, the herring mainly fed on overwintering stages of Calanus finmarchicus, i.e.…”
Section: Introductionmentioning
confidence: 99%